PEMETAAN CAPAIAN PEMBELAJARAN DAN MATERI AJAR PAI DAN BUDI PEKERTI ELEMEN AKHLAK DALAM KURIKULUM MERDEKA: (Mapping Learning Outcomes and Teaching Materials of PAI and Ethics Elements of Morality in the Independent Curriculum) - Fauzia Adnin, Gina; Fakhruddin, Agus; Subakti, Ganjar Eka (Universitas Yudharta Pasuruan, 2024)
Morals as an element in Islamic Education and Character subjects in the Independent Curriculum have continuous learning outcomes and teaching materials from primary to secondary education levels. However, moral crises such as student brawls, bullying, and so on, are still widespread in the school environment. It is hoped that the moral elements in Islamic Education and Characteristics can be a solution to this problem. This research aims to map learning outcomes and teaching materials for moral elements in the Independent Curriculum. The focus of the study includes morals towards Allah SWT, fellow humans and oneself, to ensure continuity between learning outcomes and teaching materials with student development and Islamic teachings about morals. This research uses a qualitative approach with content analysis methods on curriculum documents and PAI and Budi Pekerti textbooks in the Merdeka Curriculum version. The results of the research produced a comprehensive mapping of learning outcomes and PAI teaching materials and moral elements in the Independent Curriculum which are in line with student development and the values ​​of Islamic teachings.